PENEGAKAN HUKUM TERHADAP PROSTITUSI DI KOTA PEKANBARU - Ferly, Bobby; ', Erdianto; ', Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Factors causing the happening of prostitution is because economic factor that that womans born and enlarged by in impecunious environment, factor of sosiological like existence of social justice and urbanization, psychological factor like feeling to wish to revenge, lazy work and maniac sex and also expanding this prostitution It become various practice under cover like have massage parlour mask to and of spa (solus per aqua), karaoke, and cafe. In this case to straightening of law to prostitution in Town of Pekanbaru become problem and the importance of enforcement of law to the prostitution in Town of Pekanbaru. there is fundamental three things able to be concluded is. First, Enforcement Of Law To Prostitution in Town of Pekanbaru, that all done/conducted by law enforcement agencies punish in Enforcement of law to prostitution in Town of Pekanbaru not yet walked properly, Both, resistance met in straightening of law to prostitution in Town of Pekanbaru is factor of apparatus protected peacemaker or of government officer side using all way of to get items and lack of authority Set Of Police of Pamong District public service to fight against doing an injustice badness of this morale, Third, effort overcome this resistance is by making place rehabilitate and strive and preventif of represif by side] of apparatus of law. Suggestion Writer, First, expected to side of apparatus law doing eradication in this prostitution doing an injustice so that remain to undergo each;every regulation of applicable law. second, the needing of like agency enforcer of coherent law and dare to fight against prostitution doing an injustice, Third, the needing of facility rehabilitate and enableness of prostitute, it self prostitution consumer and pimp.Keyword: Enforcement - Law – Prostitute